2008
DOI: 10.1111/j.1365-2036.2008.03856.x
|View full text |Cite
|
Sign up to set email alerts
|

The cost‐utility of high dose oral mesalazine for moderately active ulcerative colitis

Abstract: SUMMARY BackgroundMesalazine (mesalamine) is standard first line treatment for moderately active ulcerative colitis (UC). Recently, doubling the mesalazine dose (Asacol 4.8 g ⁄ day) was shown to improve efficacy with no increase in adverse events. The cost-effectiveness of this strategy remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…A British cost-utility analysis suggested that high-dose mesalamine is more cost-effective than standard-dose mesalamine over 12-weeks in patients with moderate UC. 69 However, the small incremental benefit with high-dose mesalamine should be discussed with patients in the context of potential risks associated with delaying more effective, albeit immunosuppressive therapy. The benefit of continuing high-dose mesalamine for maintenance of remission is unclear, with moderate confidence in estimates supporting a small benefit, over standard-dose mesalamine.…”
Section: Questionmentioning
confidence: 99%
“…A British cost-utility analysis suggested that high-dose mesalamine is more cost-effective than standard-dose mesalamine over 12-weeks in patients with moderate UC. 69 However, the small incremental benefit with high-dose mesalamine should be discussed with patients in the context of potential risks associated with delaying more effective, albeit immunosuppressive therapy. The benefit of continuing high-dose mesalamine for maintenance of remission is unclear, with moderate confidence in estimates supporting a small benefit, over standard-dose mesalamine.…”
Section: Questionmentioning
confidence: 99%
“…Recognizing increased doses in the management of active UC, Buckland compared the cost-effectiveness of low-dose versus high-dose mesalazine. The investigators found that using 4.8 g/day in comparison with 2.4 g/day was cost saving and improved QoL because of improved remission rates [44]. This is, however, controversial, as efficacy is not consistently higher with higher oral doses.…”
Section: Compliancementioning
confidence: 91%
“…enteric coated products) are generally employed to maximise drug delivery to the affected regions while minimising systemic absorption. 5-ASA is generally administered at the dosage regimen of 2.4 g/day, even though recent clinical trials have convincingly demonstrated that by doubling the standard dose of mesalamine, both safety and efficacy and hence cost-effectiveness can be improved, with no increase in adverse events (Buckland and Bodger, 2008). However, most of the oral formulations currently available on the market are associated with a number of limitations, mainly a relatively low drug dosage (generally 500 mg 5-ASA/unit).…”
Section: -Asa Treatment Requirementsmentioning
confidence: 99%